Experiences of female academics in Australia during COVID-19: Opportunities and challenges - Watson, Rashmi; Singh, Upasana; Nair, Chenicheri Sid (Journal of University Teaching and Learning Practice, 2022)
An online survey collected data on a range of female academic experiences globally gaining 260 responses with 144 Australian specific academics’ responses (55% of total responses). The pandemic has highlighted positive opportunities such as online teaching and skill development, flexibility, time efficiency, increased collaboration, and time for research. In terms of challenges identified responses indicate an increased workload, less motivation for career progression, and perceptions of greater and obvious gender disparity and bias against female academics. Australia is often referred to as a ‘lucky country’ which can further be enriched though fostering its rich and diverse female academic community into the future. Rapid measures to support women immediately and with longer-term solutions that address gender equity is critical for female academics to ensure future engagement of female academics for positive economic and social growth as a nation.